2021
DOI: 10.15578/iaj.16.1.2021.35-42
|View full text |Cite
|
Sign up to set email alerts
|

DIETARY ORGANIC MINERAL INFLUENCES THE GROWTH, FEED UTILIZATION AND VERTEBRAL MINERAL CONTENT OF WILD GOLDEN RABBITFISH, Siganus guttatus

Abstract: The positive effect of organic mineral as a dietary mineral source in aquafeed has been recently reported on several species. Nevertheless, the influence of organic minerals on rabbitfish has not yet been determined. The purpose of the present study was to evaluate the effects of different doses of organic mineral on growth and survival, and mineral content in vertebrae of golden rabbitfish, Siganus guttatus. Three diets were formulated containing 0.5%, 1.0%, and 2.0% organic material (OM). A control diet (OM0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…On the other hand, the results noted that the FCR was higher in the fish fed on diets containing RH, and this was accompanied by a decrease in growth rates compared to the fish fed on the control (C). These results are in line with those of Laining and others (22) , who studied rabbitfish (Siganus guttatus) and confirmed that the amount of hornwort (Ceratophyllum sp.) in the diet increased the FCR value.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, the results noted that the FCR was higher in the fish fed on diets containing RH, and this was accompanied by a decrease in growth rates compared to the fish fed on the control (C). These results are in line with those of Laining and others (22) , who studied rabbitfish (Siganus guttatus) and confirmed that the amount of hornwort (Ceratophyllum sp.) in the diet increased the FCR value.…”
Section: Discussionsupporting
confidence: 92%
“…In another investigation, Catfish was found to have better growth performance when fed with 'Azolla' grown from wastewater, replacing up to 10 g kg -1 of fishmeal protein (Rahmah el.al 2022). In contrast, Laining et al (2016) reported rates parallelling those of the control group when using up to 30% of Ceratophyllum weed meal in the growth diets of rabbitfish. The amino acid content of the feed ingredients can be considered among the reasons for these growth differences.…”
Section: Discussionmentioning
confidence: 81%
“…3 Essential amino acids values of soybean meal, fish meal, and wheat meal were obtained from NRC (2011).4 Essential amino acids values of C. demersum meal were obtained fromLaining et al (2016). * CDM crude protein, crude lipid, crude fibre, ash, and dry matter values analysed in our study; SBM, FM, and WM values obtained from NRC (2011).…”
mentioning
confidence: 99%
“…These favorable impacts on development and feed efficiency in several fish species may be caused by the highest concentrations of essential amino acids and crude proteins found in the aquatic weeds [54,55]. Contrarily, it has been reported that using C. demersum weed meal up to 30% of the inclusion level in rabbit fish growth diets led to growth rates that were comparable to those of the control group [56]. Kiziloğlu et al [57] also noted a tendency for fish growth performance and feed utilization to decline when macrophyte content in diets increased.…”
Section: Discussionmentioning
confidence: 99%